EVALUASI PENGUATAN NILAI KARAKTER PEDULI SOSIAL DAN CINTA TANAH AIR PADA SISWA MELALUI MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS VII SMP LABORATORIUM UNDIKSHA - Dewi, Ketut Erliana; Lasmawan, I Wayan; Utami, Anak Agung Istri Dewi Adhi (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2025)
The purpose of this study was to analyze the implementation strategy for strengthening the character values ​​of social care and patriotism, identify the obstacles faced by the school, and explain the forms of policy follow-up efforts undertaken by the school in this character strengthening strategy for seventh-grade students at SMP Laboratorium Undiksha through the Pancasila Education subject. This study used a qualitative descriptive method with data collection techniques through interviews, observation, and documentation. Qualitative data analysis was conducted through the steps of data collection, reduction, presentation, and drawing conclusions. The results showed that SMP Laboratorium Undiksha has several structured and proven successful character strengthening strategies. These strategies include the 5S Habitual Program (Smile, Greet, Say Hello, Be Polite, and Courteous), the 4 Magic Words Program, the Healthy Friday and Meditation Program, and the Co-curricular and Inclusive Program. Character development is formally evaluated through homeroom teacher meetings every mid-semester. However, there are obstacles faced by all school members in its implementation, requiring ongoing evaluation to improve the character of social care and patriotism in the future. Keywords: Strengthening Character Values, Social Care, Love of the Homeland